Considerations on the use of the terms radiosensitivity and radiosusceptibility. (21st June 2018) - Wojcik, Andrzej; Bouffler, Simon; Hauptmann, Michael; Rajaraman, Preetha
Abstract: The separate use of the terms 'radiosensitivity' and 'radiosusceptibility' has been suggested to describe variability in the risk of, respectively, adverse tissue reactions (deterministic effect) following radiotherapy and radiation-induced cancer (stochastic effect). The aim of this note is to present arguments against such distinction. We feel that it is premature to make a concrete final judgement on these definitions because of the limited understanding of the mechanisms underlying individual sensitivity to both radiation-related cancers and radiation-related tissue injury. Moreover, the exclusive application of 'radiosensitivity' in relation to deterministic effects and the term 'radiosusceptibility' in relation to cancer carries the risk of being wrongly interpreted as evidence for a high, genetically driven sensitivity to radiation in all patients who develop adverse tissue reactions and a high genetic susceptibility to cancer in those who develop radiation-induced malignancies. There is a need for further research to better define these phenomena and their interrelationships.